FOOT ARCH MEASUREMENT SYSTEM FOR SPINAL AND GAIT ABNORMALITIES DETECTION - TJANDRA - NIM : 13213140 , RONNIE
Spinal and walking disorders are closely related to the posture of the foot. Abnormal foot postures potentially injure the feet and other organs during heavy, complex, and repetitive activities. This abnormality also results in gait abnormalities and may indicate spinal abnormalities. Parameters that characterize the type of foot is called Arch index that divide foot into 3 types ie normal, flat, and high arch foot. Arch index is defined as the ratio of the middle footprint to the entire footing area. Measuring foot type is usually done in the hospital by using millimeter paper that has been stepped on by patients whose soles have been smeared by ink. The area of the footprint on stepped paper is counted in many boxes for the Arch Index calculation. This method is less practical and inconvenient for patients and medical experts because it must smear the soles of the feet and manual calculation of the area. To overcome the above problem, ARCHINA is created, a tool that can measure Arch index value without using ink and do not need manual counting. This tool consists of Arch index panel, controller, seven segment display, and footprint display on monitor. Once implemented, ARCHINA was tested with various press combinations as well as subjects weighing about 100 kg and calculating the Arch index value of 10 pairs of subject feet. The test results showed that this tool can be used for patients weighing about 100 kg, and able to calculate arch index value with average error of 14.8%. It is also more convenient to use compare to ink method. Keywords